Building Diverse and Inclusive Teams in Orthopaedic Surgery: Creating a Culture that Supports Diversity of Background and Thought - Ashebo, Leta; Flynn, John M. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Orthopaedic surgery has remained one of the least diverse medical specialties for decades. This reality drives our division’s targeted efforts to build more inclusive clinical and research teams. These efforts include promoting a pipeline of diverse talent through early, deliberate recruitment and prioritizing sponsorship as an advocacy tool for underrepresented backgrounds in medicine. Through this process, we have made sure to uphold curiosity and accountability. Here we seek to describe how we have used these considerations and efforts to work towards making the orthopaedics division we inherited more representative of our patients and communities.